Implementasi Metode Extreme Programming (XP) dalam Pengembangan Aplikasi Ujian Online Berbasis Web - Rubiah, Siti; Supriadi, Fidi; Junaedi, Dani Indra (Yayasan Pendidikan Tanggui Baimbaian, 2024)
Assessment of learning outcomes is an important part of education because it serves as a means to determine students' competency achievements. Many educational institutions still use conventional methods or written exams with paper and writing instruments for assessment. This method is ineffective in terms of time and cost and cannot prevent cheating during the exam. This challenge is also faced by SMP NU Darul Falah Subang. One solution to address these problems is to utilize information systems through the development of an Online Exam application. The method used in developing this application is Extreme Programming (XP). The XP method was chosen because it requires relatively short development time, is flexible, cost-effective, and suitable for use by small-scale teams. The aim of this research is to implement the Extreme Programming (XP) method in the development of an Online Exam application.